Values Added to Taekwondo Training Program for Life Quality Development in Underprivileged Children - Chumpen, Kanittha (Academic Journal of Thailand National Sports University, 2022)
The objectives of this research were 1) to study taekwondo training program improve a better life quality of underprivileged children, and 2) to compare life quality before, during, and after training. Life quality received from the Taekwondo training was classified as the aspects of self-esteem, sportsmanship, emotional quotient, social adjustment and physical fitness. Samples were 60 underprivileged students of Chalermprakiet 48 Punsa School, Lumphun province, volunteered to participate in the study. They were divided into 2 groups as the experimental group and the control group, 30 of each. Research tools, taekwondo training program for life quality development, designed by the researcher. The experiment carried out for 16 weeks of 2 periods/a week all 32 lessons and test before trial, during trial and after the trial. Test composed of self esteem, sportsmanship, emotional quotient (E.Q.), social adjustment, and physical fitness. Statistics used were frequency, percentage, mean, standard deviation, Mixed ANOVA. The results were as follows: 1) the taekwondo training program positively influenced life quality of underprivileged children by significantly increasing the aspects of sportsmanship, emotional quotient (E.Q.), social adjustment and physical fitness, at the .05 level. 2) In comparing the life quality of the experimental group was significantly better than the control group in sportsmanship, social adjustment, and three variables of physical fitness such as sit and reach, push up and walk/run 1.6 miles at the .05 level. However, self esteem emotional quotient (E.Q.) and two variables of physical fitness aspect as to BMI and abdominal curl were not significantly different. The recommendations from the research were: Practicing Taekwondo in underprivileged children has improved their life quality. Therefore, it is suggested that Taekwondo be practiced by other underprivileged children in other different schools. Moreover, school curricular should contain Taekwondo as the guideline to child development in all parts. Child related organizations should promote Taekwondo in children, including applying the sport in developing their skills and quality of life.